2019
DOI: 10.1182/bloodadvances.2018021014
|View full text |Cite
|
Sign up to set email alerts
|

Malglycemia is associated with poor outcomes in pediatric and adolescent hematopoietic stem cell transplant patients

Abstract: Malglycemia (hypoglycemia, hyperglycemia, and/or glycemic variability) in adult hematopoietic stem cell transplant (HSCT) recipients is associated with increased infection, graft-versus-host disease, organ dysfunction, delayed engraftment, and mortality. Malglycemia has not been studied in pediatric HSCT recipients. This study aimed to characterize the incidence and consequences of malglycemia in this population. Medical records for a cohort of 344 patients, age 0 to 30 years, who underwent first HSCT from 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…This retrospective cohort study demonstrates that glycemic variability, as measured by CV, is common in pediatric patients undergoing HSCT, and that it is associated with increased risk of infection and critical illness. These associations are consistent with research describing malglycemia as a whole, both in adult and pediatric HSCT patients 1‐3 . Associations between glucose CV and mortality were less clear.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This retrospective cohort study demonstrates that glycemic variability, as measured by CV, is common in pediatric patients undergoing HSCT, and that it is associated with increased risk of infection and critical illness. These associations are consistent with research describing malglycemia as a whole, both in adult and pediatric HSCT patients 1‐3 . Associations between glucose CV and mortality were less clear.…”
Section: Discussionsupporting
confidence: 86%
“…It is possible that patients with malignant underlying diagnoses were more tolerant of the stress associated with HSCT preparation due to their prior treatment with chemotherapy, while for nonmalignant HSCT patients, HSCT preparation may have been more disruptive. While our prior research evaluating risk factors for pre‐HSCT malglycemia identified underlying malignant diagnosis and adolescent age as risk factors, these were not associated with pre‐HSCT glucose CV; thus, these findings were likely driven by hyperglycemia and not variability 3 …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Although further research is required to validate, our proposed model of inflammation-induced PTDM is outlined in Figure S2. (Table S2) [1,2,5,6,12,16]. With the clinical importance now established, it is time to shift focus from examining the incidence of PTDM, and begin to study the mechanistic causes for hyperglycemia and potential therapeutic options to prevent or treat metabolic complications after HCT.…”
Section: Resultsmentioning
confidence: 99%
“…The development of PTDM was independent of corticosteroids and was associated with a decrease in OS and DFS. At least two other prospective and several retrospective studies have confirmed the high incidence and negative consequences of PTDM after HCT (Table S2) [1,2,5,6,12,16]. With the clinical importance now established, it is time to shift focus from examining the incidence of PTDM, and begin to study the mechanistic causes for hyperglycemia and potential therapeutic options to prevent or treat metabolic complications after HCT.…”
Section: Discussionmentioning
confidence: 99%